The illustrated humanism of Toribio Rodríguez de Mendoza - González Villacorta, Steves (2023)
This article shows the studies that have been carried out around the thought of Toribio Rodríguez de Mendoza and how an attempt has been made to present his ideas related to philosophy. Comparative Enlightenment ideas range from English to German thought in order to find influences. Likewise, the relationships between the Peruvian enlightened people and their humanist thought are analyzed to determine the exchange of philosophical ideas in this context.